Profile and outcome of children with inborn errors of metabolism in a tertiary pediatric intensive care unit in South India - Sivaraman, Rajakumar Padur; Balakrishnan, Umamaheswari; Chidhambaram, Sathya; Tarikare, Shruthi; Sankaranarayanan, Shuba (Indian Journal of Child Health, 2019)
Introduction: Inborn errors of metabolism (IEM) can present as acute metabolic emergencies resulting in significant morbidity or death. Good intensive care supportive management and specific metabolic crisis treatment by tertiary pediatric intensive care unit (PICU) play a crucial role in optimizing the outcomes. Objectives: We aimed to study the clinical profile and outcome of children with IEM presenting as an acute metabolic crisis in a tertiary PICU. Methods: This retrospective descriptive study was conducted in a tertiary care center in south India between June 2016 and December 2018. We included children admitted in PICU as medical emergency and diagnosed to have IEM either earlier or at the time of PICU presentation by biochemical testing (basic testing and tandem mass spectrometry [TMS], gas chromatography-mass spectrometry [GCMS] and high-performance liquid chromatography [HPLC], and/or specialized testing) and/or molecular analysis. Clinical profile, details of diagnostic workup, and outcome were collected and analyzed. Results: Out of 2815 children admitted in PICU, 15 had IEM (0.9%). Median (interquartile range) age of presentation was 15 months (10–30 months). Consanguinity was found in 80%. The most common disorder was protein metabolic disorder. Seven patients were diagnosed in the newborn period, five during evaluation for developmental delay before PICU admission, and three were newly diagnosed during PICU admission. Supportive therapy of invasive/non-invasive ventilation and peritoneal dialysis was initiated in 10 and 4, respectively. Special formula was started in nine patients. Five (33%) died in spite of intensive care management. TMS, GCMS, and HPLC yielded definitive diagnosis in 12 (80%) patients. Molecular analysis was done in 12 patients. Conclusion: The most common cause for metabolic crisis in PICU is due to protein metabolic disorder. Aggressive intensive care and IEM directed therapy can be lifesaving, but still, the mortality is high.